Perancangan Sistem Pengendalian Kualitas Menggunakan Pendekatan Statistical Process Control di PT X - Matthew Marcelieno; Yurida Ekawati (Teknik Industri Universitas Ma Chung, 2021)
PT. X is a flavored beverage company facing the challenge of controlling the quality of its products due to the lack of a proper control system. The company experienced a high percentage of defective products in recent months, with a defect rate of 0.419% from September 2019 to December 2020. To address this issue, a quality control system was designed, utilizing a business process chart with a statistical process control (SPC) approach. The system involved the use of a checksheet for data collection and a control chart to regulate the average and variation of volume, pH, brix, and defective products. Pareto analysis was performed to identify potential causes of defective products, and efforts were made to address issues related to dented cups and leaky lids. Improvements made to the system proved successful in lowering the defect rate. The proposed quality control system was presented in the form of Standard Operating Procedures (SOP), and the processes of volume, pH, and brix are now under control.